2023
DOI: 10.1073/pnas.2303836120
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of cis -regulatory sequences and transcriptional divergence of duplicated genes in soybean

Chao Fang,
Mingyu Yang,
Yuecheng Tang
et al.

Abstract: Transcriptional divergence of duplicated genes after whole genome duplication (WGD) has been described in many plant lineages and is often associated with subgenome dominance, a genome-wide mechanism. However, it is unknown what underlies the transcriptional divergence of duplicated genes in polyploid species that lack subgenome dominance. Soybean is a paleotetraploid with a WGD that occurred 5 to 13 Mya. Approximately 50% of the duplicated genes retained from this WGD exhibit transcriptional divergence. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…Activating ACRs were more likely to act proximally compared to repressing ACRs (Figure 3K). Notably, we identified three known activating CREs expressed in different tissues and involved diverse developmental pathways (Figure 3N-P), such as in seed tissues, 35 ASYMMETRIC LEAVES2-LIKE 18 (ASL18) , a known root nodule symbiosis marker, 36 and a pod shattering-resistance related gene 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Activating ACRs were more likely to act proximally compared to repressing ACRs (Figure 3K). Notably, we identified three known activating CREs expressed in different tissues and involved diverse developmental pathways (Figure 3N-P), such as in seed tissues, 35 ASYMMETRIC LEAVES2-LIKE 18 (ASL18) , a known root nodule symbiosis marker, 36 and a pod shattering-resistance related gene 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Chromatin accessibility levels of the 5′ ACRs of active genes are positively correlated with the expression levels of the genes 77 . In addition, enhancer functions of ACRs located outside of promoter regions, including those located in the introns, have been demonstrated in several plant species 25 , 71 , 78 . Therefore, the number of ACRs and the chromatin accessibility level of each ACR can be used to measure and compare the activity and divergence of duplicated genes or homoeologous genes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the number of ACRs and the chromatin accessibility level of each ACR can be used to measure and compare the activity and divergence of duplicated genes or homoeologous genes. We recently demonstrated that gain or loss of DNA sequences and mutation of cis -regulatory elements located within flanking ACRs can change the balance of the expression level and/or tissue specificity of duplicated genes in soybean 25 . In the current study, we found that the dominant subgenome A contains a greater number of total MHSs and MHS per gene than the submissive B/C/D subgenomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to human or model plants (e.g., Arabidopsis), there are many databases with abundant sequencing data for understanding the function of noncoding regions, such as the human ENCODE (https://www.encodeproject.org accessed on 1 May 2024) and the Arabidopsis Cistrome database [20]. Although soybean also has abundant DNA resequencing data characterizing the single nucleotide polymorph (SNP) or structural variation (SV) at the genomic level, for example, the recently published soybean PAN-genome data [21], few high-throughput sequencing data (e.g., ATAC-seq) [22][23][24] have been aimed at finding these functional non-coding elements (e.g., motifs) in the soybean genome. Compared to the ChIP-seq method [14], a traditional strategy for discovering new motifs, DAP-seq [15] is able to select the DNA fragments directly bound by the recombinant TF in vitro, which showed some advantage over the ChIP-seq in finding motifs.…”
Section: Discussionmentioning
confidence: 99%